2006
DOI: 10.1103/physreva.73.033614
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical selection in developing fermionic pairing

Abstract: We consider evolution of a Fermi gas in the presence of a time-dependent BCS interaction. The pairing amplitude in the emergent BCS state is found to be an oscillatory function of time with predictable characteristics. The interplay of linear instability of the unpaired state and nonlinear interactions selects periodic soliton trains of a specific form, described by the Jacobi elliptic function dn. While the parameters of the soliton train, such as the period, amplitude, and time lag, fluctuate among different… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
82
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(89 citation statements)
references
References 28 publications
6
82
1
Order By: Relevance
“…However, as discussed in Ref. 12, a time window for τ 0 exists in which the constraint for avoiding the overheating is compatible with that of a sudden switching-on of the interaction.…”
Section: The Modelmentioning
confidence: 93%
See 3 more Smart Citations
“…However, as discussed in Ref. 12, a time window for τ 0 exists in which the constraint for avoiding the overheating is compatible with that of a sudden switching-on of the interaction.…”
Section: The Modelmentioning
confidence: 93%
“…Time-dependent mean-field theory As discussed in Ref. 12, the nonequilibrium evolution of the fermion system can be analyzed within a timedependent mean-field theory. To this end we introduce the pairing function ∆(t) = g k ĉ −k↓ĉk↑ , where the average is taken over the quantum state of the system at time t. After the mean-field decoupling is performed, the BCS Hamiltonian (1) reduces to a sum of time-dependent…”
Section: The Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies, motivated by experiments in cold atomic fermions, focused on quantum quenches, nonequilibrium conditions created by a sudden change in the superconducting coupling strength. Barankov et al [7], in a paper that set off a surge of modern research in this long-standing problem [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] in the context of quantum gases, found that for initial conditions close to the unstable normal state, the order parameter exhibits large anharmonic periodic oscillations.…”
Section: Introductionmentioning
confidence: 99%